Intervenção centrada na família: influência nas habilidades comunicativas e interativas da criança com transtorno do espectro autista e no empoderamento parental - Oliveira, Jéssica Jaíne Marques de (2016)
The Autism Spectrum Disorder (ASD) is characterized by impairments in socio communicative and behavioral dimensions. The early the diagnosis is made and started the interventions, the better will be the outcomes. The interventions must be addressed to the core needs of each subject and consists in providing, by a transdisciplinary team, services directed not only to the child, but also to the whole family. Including the family as critical piece of the intervention places them as an active agent, working side by side with the professionals in favor of the son s development. Therefore, it is necessary that the parents receive a specific training about interventions and autism, retaining this knowledge. The Family empowerment is a terminology to designate this continuous ability of groups or subjects to act for their own benefit to achieve better control over their lives and faiths. Moreover, the literature has shown that family empowerment is highly associated to gains in interventions with children with autism, highlighting its importance for intervention´s effectiveness. This study aims to measure the effects of an intervention based on parents training about the development of communicative and interactional skills of their autistic son, as well as verify the influences of this kind of intervention over family empowerment. It was used an quase experimental design, A-B type, in a single case research, where the participants was a child with ASD and 15 months old, his father and his mother. The results showed that parental training program promoted an increase in socio communicative skills of the mother-child dyad, both in joint attention and topic sharing, as in affective contact. It was observed an increase in parental empowerment levels between pre- and post-intervention, understood as an influence of the training program. Finally, it is concluded that the family centered intervention, more specifically the parental training, is shown as an available possibility to promote early development of sociocomunicativas skills of children with ASD.